A multi-level adaptation scheme for hierarchical bearing fault diagnosis under variable working conditions. (July 2022) - Su, Kaige; Liu, Jianhua; Xiong, Hui
Abstract: Bearing fault diagnosis is important during the operation of mechanical equipment. Traditional deep-learning-based methods afford excellent diagnostic results if the training and test samples are of similar distribution. Thus, the datasets used for training and testing are collected under the same working conditions. However, when the working conditions change, a fault diagnosis model trained using such a training set cannot be directly applied to the test set. In addition, existing classification methods ignore the hierarchical structure of bearing fault categories, thus treating all categories equally. To address these issues, we present a new form of branch multi-level adaptation based on a convolutional neural network (BMACNN model). A branch structure is added to a one-dimensional CNN to permit hierarchical diagnosis of bearing faults via multiple output layers. The multiple kernel variant of the maximum mean discrepancy is used to regularize the loss function, thus reducing distributional distances among the domains of multiple levels. We tested the BMACNN model using six distinct transfer fault diagnostic scenarios of the Paderborn dataset. The BMACNN robustly adapted to variable working conditions and was superior to other methods. Highlights: We present a multi-level adaptation based convolutional neural network model for bearing faults diagnosis. A branch structure is added to output predictions in hierarchical diagnosis. The maximum mean discrepancy is used to regularize the loss function. The model is tested with six distinct transfer fault diagnostic scenarios under variable working conditions.